2019
DOI: 10.1161/jaha.119.013450
|View full text |Cite
|
Sign up to set email alerts
|

Age‐ and Lesion‐Related Comorbidity Burden Among US Adults With Congenital Heart Disease: A Population‐Based Study

Abstract: BackgroundAs patients with congenital heart disease (CHD) are living longer, understanding the comorbidities they develop as they age is increasingly important. However, there are no published population‐based estimates of the comorbidity burden among the US adult patients with CHD.Methods and ResultsUsing the IBM MarketScan commercial claims database from 2010 to 2016, we identified adults aged ≥18 years with CHD and 2 full years of continuous enrollment. These were frequency matched with adults without CHD w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 31 publications
1
48
2
Order By: Relevance
“…Considering other predictors of employment, we found that work participation was very strongly correlated with private insurance coverage, suggesting that a prior estimate of 49% employment among United States adults with CHD covered by private insurance plans may have overestimated work participation in the all-payor adults with CHD population. 7 Furthermore, we found that married adults with CHD were twice as likely to work as patients who were single. This result may represent selection into marriage on the basis of greater independence or social functioning, or discrimination on the marriage market against adults with CHD whose health condition limits their ability to work.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Considering other predictors of employment, we found that work participation was very strongly correlated with private insurance coverage, suggesting that a prior estimate of 49% employment among United States adults with CHD covered by private insurance plans may have overestimated work participation in the all-payor adults with CHD population. 7 Furthermore, we found that married adults with CHD were twice as likely to work as patients who were single. This result may represent selection into marriage on the basis of greater independence or social functioning, or discrimination on the marriage market against adults with CHD whose health condition limits their ability to work.…”
Section: Discussionmentioning
confidence: 75%
“…CHD is known to limit employment participation, even for relatively simple defects, and even after definitive surgical treatment. 7,21 However, prior studies in the United States have frequently been limited by tracking employment only among adults with CHD under cardiology follow-up. 3 With loss to cardiology follow-up becoming increasingly common as adults with CHD age, alternative strategies are needed to produce population-based estimates of employment among adults with CHD, as well as factors affecting employment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adults with congenital heart disease (CHD) are a rapidly increasing population, 1 have many comorbidities, 2 and require frequent monitoring. 3 However, little is known about their ambulatory health care use and associated costs in the US.…”
Section: Introductionmentioning
confidence: 99%